Factors that Affect Creating of Competitive Advantage for Trade Business in Xayabury District, Xayabury Province - sukphaly, saysana; CHANTHAVONE, Thongphanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purposes of study were: 1) to study trade business competition situation of entrepreneurs, 2) to study a creation of a competitive advantage for trade business of entrepreneurs, and 3) to investigate factors that affect a creation of a competitive advantage for trade business in Xayabury district, Xayabury province. The research sample was 160 peoples from trade business of entrepreneurs by using questionnaires as data collection instrument and statistics were used to analyze frequency, percentage, mean, standard deviation and stepwise multiple linear regression. The research found that: 1) trade business in Xayabuly City, Xayabuly Province, faces moderate competitive pressure with the strongest force coming from existing competitors within the industry, followed by the pressure from the entry of new competitors, the bargaining power of suppliers of goods/raw materials, the bargaining power of buyers, and lastly, the threat of substitute goods. 2) The creation of a competitive advantage of trade business entrepreneurs in in Xayabuly City, Xayabuly Province is at a high level, the highest mean is the trading business difference in bringing new commodities different from the competitors to the market to satisfy the customers. To quickly response to the needs of clients, it is necessary for the trading businesses to present new products. Trading businesses need to emphasize targeting markets by building good collaboration and friendship with clients. Trading business need to have a strategy in lowering operation costs by using resources effectively. 3) Factors affecting the creation of a competitive advantage for trading business in Xayabury district, Xayabury province, consist of six factors such as: proactive factor, current competitor factors, competitive strength factors, risk tolerance factors, political-legal factors and threat factors from substitute products. These factors are directly interconnected with the creation of a competitive advantage, except, political-legal factors of the entrepreneurs in Xayabuly District, Xayabuly Province.